Student Ratings and Course Modalities - Chuck Dziuban; Patsy Moskal; Annette Reiner; Adysen Cohen (Online Learning, 2023)
This article examines the impact of course modality on student evaluation of courses and professors. Data were collected through the Student Perception of Instruction end of course rating form at the University of Central Florida (UCF), which contains nine items and maintains student anonymity. The findings indicate that while course modality accounts for only 1% of the variance in student evaluations, there is strong internal consistency and reliability in the rating scale. The distribution of ratings showed a concentration of scores at the high end, resulting in a high variability coefficient. However, when the long tail of low ratings was removed, the mean increased and the distribution became more symmetric, affecting various psychometric indices. The correlation matrices among the items revealed a single factor solution for each modality, suggesting that students tend to rely on a general impression when rating their courses. The multidimensional scaling process identified underlying categories such as structure, course climate, engagement, and consideration, even though students did not explicitly differentiate these elements in their responses. The study concludes that course modality has minimal influence on overall student ratings, a finding consistent across different time periods, including the COVID-19 pandemic. Although a single factor captures students' general evaluations, underlying categories shape their responses. The article also presents a classification model that predicts student ratings based on the scale items. This research addresses the complex dynamics of student evaluations, highlighting the nuanced relationship between course modality, student perceptions, and the underlying factors influencing their ratings.